Multiple Intraspecific Variations of Mitochondrial Genomes in the Green-Tide Forming Alga, Ulva compressa Linnaeus (Ulvophyceae, Chlorophyta) - Liu, Feng; Melton, James T. III; Lopez-Bautista, Juan M.; Chen, Nansheng (Frontiers in Marine Science, 2020)
To gain further insights into intraspecific evolution of Ulva mitochondrial genomes, the mitogenomes of three morphotypes of the green-tide forming alga, Ulva compressa Linnaeus from China and United States, were sequenced and compared with the available data from Ulvophyceae. The U. compressa mitogenomes displayed substantial genome size variation at intraspecific level ranging from 61,700 to > 66,587 bp, due to different acquisitions of foreign DNA fragments, gain or loss of both group I and II introns, and non-coding intergenic spacer regions. The U. compressa mitogenomes harbored variable gene content ranging from 69 genes (including orfs) in Uco1 to 76 in Uco5, and contained different intron content from 4 introns in Uco3 and Uco4 to 7 in Uco1. A total of 63 genes and only two group IB introns (intron cox1-1107 and cox1-1125) were shared by these five mitogenomes. The U. compressa mitogenomes accumulated many more inverted repeat (IR) elements, ranging from 45 in Uco1 to 88 in Uco2, than that of the other Ulva species (3–34). A locally collinear block of eight genes (rps11-rps19-rps4-rpl16-trnR-trnQ-trnE-trnS) with the size of 3,631 bp has been inverted only in Uco1 indicating that the rearrangement event happened after its divergence from Uco2–5 and might be related to a specific IR element. The majority of the common genes ( 76%) displayed high identity (>98%) among these five mitogenomes, while some low values were observed in six genes mainly due to duplication and insertion/deletion mutations of small DNA fragments. Our study presented the first case of multiple intraspecific variations in ulvophycean mitogenomes, and indicated that the mitogenome will be a valuable tool for understanding the native or non-indigenous nature of the cosmopolitan Ulva species.